Nonlinear vibration analysis of an embedded branched nanofluid-conveying carbon nanotube: Influence of downstream angle, temperature change and two dimensional external magnetic field - A.A. Yinusa; M.G. Sobamowo; A.O. Adelaja (Nano Materials Science, 2020)
In this study, non-linear thermal-mechanical stability and vibration analyses of different end-shaped single-walled carbon nanotube conveying viscous nano-magnetic fluid embedded in non-linear visco-elastic foundation under the influence of magnetic fields are presented. The development of the equation of motion was based on Euler-Bernoulli theory, Hamilton principle and nonlocal elasticity theory. The results of the analytical solutions using Galerkin decomposition differential transform method (GDDTM) were validated with existing experimental results. From the parametric studies, it was shown that decreasing the temperature difference as well as increasing the downstream angle decreased the system's stability for pre-bifurcation analysis but increased stability of the system for post bifurcation analysis. Also, the results obtained from the dynamic behaviour of the system indicated that the magnetic effect had an attenuating impact of about 45% on the system's response at any mode and for any boundary condition considered. It is hoped that this work will enhance the design and optimization of nano-devices with I, V, Y, L, K and T-shaped junctions under the influence of thermal-magneto-mechanical flow induced vibration.